Causes of Mortality and Diseases in Farmed Deer in Switzerland - Veronika Sieber; Nadia Robert; Martina Schybli; Heinz Sager; Raymond Miserez; Monika Engels; Marie-Pierre Ryser-Degiorgis (Veterinary Medicine International)
To investigate diseases and causes of mortality in Swiss farmed deer, deer found dead or shot due to diseased condition between March 2003 and December 2004 were requested for a complete postmortem examination. One hundred and sixty-two animals were submitted. Perinatal mortality, necrobacillosis in 3 week to 6 month old deer, and endoparasitosis in 6 month to 2 year old deer were identified as the most important causes of loss, followed by ruminal acidosis, which was diagnosed in 22% of deer older than 1 year. Congenital malformations were observed in 15% of deer less than 6 months old. Reportable infectious diseases known as major problems in deer farming in other countries were rare (yersiniosis, malignant catarrhal fever) or not observed (tuberculosis, chronic wasting disease). Overall, the results indicate that the Swiss deer population does not present major health problems of concern for domestic animals.